Σχεδιασμός μεταλλικού φέροντος οργανισμού ατμοηλεκτρικού σταθμού - Φασαράκης, Γιώργος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Μεταλλικών Κατασκευών, 2017)
This diploma thesis deals with the study -analysis and design –of the metal frame core of a steam-cycle coal power plant, and an interior, composite floor, under the requirements of Eurocodes (EN 1990, 1991,1993,1994 and 1998). The resolution of the building was performed using SAP2000 v.18 software, the control of adequacy of the composite slab using SymDeck Designer 2 and the design of the connections with the Power Connect rev2 software. More specifically, the structure of this paper is given below: In the first chapter, the case study, the web of regulations, a short retrospection of the history of metallic structures, as well as steel as a struxtural component are psesented. The second chapter contains the description of the building and provides information about its geometry, dimensions and structural elements. It analyzes the architecture and construction of the project and provides information about its structural system. In the third chapter, the properties of the materials that were used and the loads acting on the construction are described. Moreover, the load combinations, on which the analysis and dimensioning are based, are determined. The fourth chapter escribes the analysis and dimensioning of our structure. Initially, are described the necessary checks according to Eurocode 3. Subsequently, the software used to analyze the dynamic modal response spectrum analysis of the structure, which is SAP2000, is presented, as well as the model of the building used in SAP2000. Then, the results of checks at the Ultimate Limit State and Serviceability are presented. Finally, a check of the composite slab is made. In the fifth chapter typical joints are tested, such as the joints between column-beam, column-secondary beam, beam-secondary beam, column base plate. Finally, in the sixth and conclusive chapter of the thesis, the results are summarized and conclusions are mentioned.